The effects of public R&D subsidies on firms' innovation activities: the case of Eastern Germany - Matthias Almus; Dirk Czarnitzki (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This study analyzes the effects of public R&D policy schemes on the innovation activities of firms located in Eastern Germany. The main question in this context is whether public funds stimulate R&D activities or simply crowd out privately financed R&D. Empirically, we investigate the average causal effects of all public R&D schemes in Eastern Germany using a non?parametric matching approach. Compared to the case where no public financial means are provided, it turns out that firms increase their innovation activities by about four percentage points.
Keywords: O38; O31; C41; 330; Public Innovation Subsidies; Non?parametric Matching; Forschungs- und Technologiepolitik; Forschungssubvention; Wirtschaftspolitische Wirkungsanalyse; Industrielle Forschung; Innovation; Schätzung; Neue Bundesländer; self selection; Selbstselektion